Factors influencing the use of ICT in teaching among secondary school teachers in Aba North District, Nigeria - Augustine, Nwosu (2018)
This study examined the factors influencing the use of ICT in teaching among secondary school teachers in aba north district, Nigeria. Using TAM as the research model, this study examined the ICT competency, accessibility of ICT, perceive usefulness, perceived ease of use, attitude toward ICT, behavioral intention to use ICT and teachers’ use of ICT in teaching in Aba north secondary schools. Questionnaires were used to collect data from a sample of 234 teachers, randomly selected from 20 secondary schools in Aba north district. Result showed that the overall mean for ICT competency construct of teachers in Aba north district is (M=2.87), which is considered moderate, indicating that teachers in Aba north secondary schools have average ICT competency. The overall mean scores of teachers’ perceived ease of use, perceived usefulness, attitude towards ICT and behavioral intention to use ICT were found to be high at M=3.54, 3.52, 3.57 and 3.55 respectively. This shows that teachers in Aba north secondary schools perceived the use of ICT to be easy and usefulness. It also shows that they have positive attitude towards ICT and good behavioral intention to use ICT in teaching. Accessibility of ICT and teachers’ use of ICT in teaching were found to be low with overall mean scores of (M= 1.69 and1.57) respectively, indicating that teachers do not have access to ICT when needed and did not use ICT in teaching. Correlation analysis found that teachers’ perceived ease of use, perceived usefulness and behavioral intention to use ICT have weak relationships with their use of ICT while ICT competency and attitude towards ICT do not have significant relationship with use of ICT. It was found that accessibility of ICT and use of ICT have a moderately strong significant relationship (rs=.414). The strength of this relationship shows that these two variables can predict each other. It can be said that accessibility of ICT predicts the use of ICT in teaching among teachers in Aba north district secondary schools. Even though teachers had moderate ICT competency, perceived ICT easy to use, useful, had good attitude towards it and good behavioral intention to use it, they still had low use of ICT in teaching probably because of low accessibility of ICT in Aba north secondary schools.